Neurofeedback Therapy in ADHD Treatment - Saputro, Dwidjo (Faculty of Psychology, Universitas Surabaya, 2011)
Psychopharmacology, especially metilfenidat, is still the main therapy to overcome ADHD problem. However, this type of psychopharmacology still has a lot of limitations. As an alternative, neurofeedback therapy is one of the forms of behavioral therapies with operant conditioning principles which train and condition the brain through its cerebral neurofeedback. This therapy is done by placing electrodes on the scalp to record cerebral neurofeedback. Neurofeedback therapy comes under neurobehavioural therapy which is designed for one to gather self-control through cerebral neurofeedback to apply in daily life. Quite a few researches have confirmed that neurofeedback therapy is beneficial and could be considered as one of therapy options for ADHD children. Terapi psikofarmaka, terutama metilfenidat, masih merupakan terapi utama untuk gangguan ADHD, meskipun terdapat berbagai kekurangan dan keterbatasan. Sebagai alternatif, terapi neurofeedback adalah salah satu bentuk terapi perilaku, dengan prinsip operant conditioning, yang bertujuan melatih dan mengondisikan otak, dengan balikan gelombang listrik otak. Terapi ini dilakukan dengan pemasangan elektroda pada kulit kepala untuk melakukan perekaman aktivitas gelombang listrik otak. Terapi neurofeedback termasuk terapi neurobehavioral yang bertujuan untuk memperoleh pengendalian diri dengan melalui pengaturan aktivitas gelombang listrik otak untuk selanjutnya diterapkan dalam kehidupan sehari-hari. Berbagai penelitian telah menunjukkan bahwa terapi neurofeedback memberikan manfaat dan dapat dipertimbangkan sebagai salah satu pilihan terapi untuk anak dengan ADHD.